Pengaruh Metode Ultrasonic Assisted Extraction (UAE) terhadap Kadar Antosianin dan Aktivitas Antioksidan Esktrak Jagung Hitam (Zea mays L.) - Christy Natalia Limbu Datu; Danang Raharjo; Bangkit Riska Permata (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to comprehensively evaluate the effect of the Ultrasound Assisted Extraction (UAE) method on anthocyanin content and antioxidant activity of black corn (Zea mays L.) extract as a source of natural bioactive compounds. The method employed was a laboratory experimental design involving extraction using 70% ethanol acidified with 1% HCl at a material-to-solvent ratio of 1:15 (b/v), with an ultrasonic frequency of 42 kHz for 30 minutes under controlled conditions. Total anthocyanin content was determined using the pH differential method, while antioxidant activity was analyzed using the ABTS method to determine the IC₅₀ value. The results showed that the extract yield obtained was 18.61%, indicating efficient extraction performance. The total anthocyanin content was recorded at 331.06 mg/100 g sample, while the antioxidant activity (IC₅₀) value was 61.47 ppm, which falls into the strong activity category. Phytochemical screening confirmed the presence of flavonoids, anthocyanins, tannins, saponins, alkaloids, and triterpenoids contributing to the antioxidant activity of the extract. Overall, these findings demonstrate that the UAE method is effective in enhancing extraction efficiency and extract quality. This study supports the utilization of black corn as a natural antioxidant source and a potential raw material for the development of functional foods and plant-based health products.